Rosario Tijeras: a look at the twentieth century Colombian violence - Ávila Arce, Dayhana; Martínez Gómez, Yamile (Rastros Rostros, 2011)
This article presents a detailed report of the process and the results from the formative research “Rosario Tijeras: A perspective from the Colombian violence in the twentieth century” of Universidad Cooperativa de Colombia, Bucaramanga, 2009, which aim is to study this novel written by Jorge Franco Ramos. This work is part of a macro research project called “Colombian political proposals in the novel of the twentieth century” which is focused on the Colombian violence literature from the rural and urban contexts. Jorge Franco in his novel, Rosario Tijeras, presents Medellin in its 80’s, heavily influenced by the power of drug trafficking that was generated as a result of violence, a reality in which a group of young people , were involved including Rosario Tijeras, a woman to whom life and death taught to defend herself with bullets and scissors. This research analyzes author experience ́s spaces and the novel, It also proposes a pedagogical approach which aims to bring the novel to the school to develop student ́s critical view of Colombian society.